Assembly of the unique Trypanosoma brucei F1-ATP synthase - Lazebnyk, Vladyslav (Jihočeská univerzita, 2022)
The catalytic F1-ATP synthase of the human pathogen T. brucei has several unique features. This essential enzyme contains three copies of the novel subunit p18 and it incorporates both subunit peptides generated by a rare proteolytic event. Therefore, we characterized genetic cell lines that deplete the only two known F1-ATP synthase assembly factors in order to gain more insight into the fascinating assembly of this parasitic enzyme.
Assembly of the unique Trypanosoma brucei F1-ATP synthase
Keywords: Trypanosoma brucei; parasite; ATP-synthase; assembly factors; p18; Trypanosoma brucei; parasite; ATP-synthase; assembly factors; p18